2009
DOI: 10.1002/bin.288
|View full text |Cite
|
Sign up to set email alerts
|

Functional communication during signaled reinforcement and/or extinction

Abstract: Schedule thinning following functional communication training (FCT) can increase treatment feasibility. Multiple-schedule arrangements are often used in this process; however, the current literature provides little information on the optimum signal arrangements. In the current study, we examined the effects of three signal arrangements (i.e., signaled FR1, signaled EXT, and signaled FR1/EXT) on rates of problem behavior at dense schedule values and during schedule thinning. At all schedule values, signaled FR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Multiple schedules have been combined with treatment interventions (e.g., FCT) to treat problem behavior maintained by access to adult attention (Fisher et al, 1998; Rooker et al, 2013), access to tangible items (Betz et al, 2013; Hagopian et al, 2005), access to edible items (Jarmolowicz, DeLeon, & Contrucci Kuhn, 2009), interruption of ritualistic behavior (Rispoli, Camargo, Machalicek, Lang, & Sigafoos, 2014), escape from academic instruction (Álvarez et al, 2014), and problem behavior maintained by automatic reinforcement (Anderson et al, 2010; Doughty et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple schedules have been combined with treatment interventions (e.g., FCT) to treat problem behavior maintained by access to adult attention (Fisher et al, 1998; Rooker et al, 2013), access to tangible items (Betz et al, 2013; Hagopian et al, 2005), access to edible items (Jarmolowicz, DeLeon, & Contrucci Kuhn, 2009), interruption of ritualistic behavior (Rispoli, Camargo, Machalicek, Lang, & Sigafoos, 2014), escape from academic instruction (Álvarez et al, 2014), and problem behavior maintained by automatic reinforcement (Anderson et al, 2010; Doughty et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, Jarmolowicz et al (2009) compared the effectiveness of mixed schedules with three variations of multiple schedules: (a) when the reinforcement component only was signaled by a specific schedule-correlated stimulus, (b) when the EXT component only was signaled by a specific schedule-correlated stimulus, or (c) when both the reinforcement and EXT components were signaled by different, specific, schedule-correlated stimuli. The results of this study suggested that signaled components were always more effective than mixed schedules; however, signaling both reinforcement and EXT did not produce significantly better effects than signaling reinforcement only.…”
Section: Considerations In Arranging Multiple Schedulesmentioning
confidence: 99%
“…In our review, we found five studies describing eight applications of FCT that used multiple schedules as a means of thinning reinforcement schedules and maintaining low rates of problem behavior (see Table). In some of the applications (5 of 8), the use of multiple schedules resulted in the successful achievement of treatment goals with FCT and extinction without supplemental treatment components (Hagopian, Toole, Long, Bowman, & Lieving, 2004;Hanley et al, 2001;Jarmolowicz et al, 2009). However similar to the previous two schedule-thinning methods, for some applications (3 of 8), treatment goals were not met until supplemental components were added (e.g., adding competing or alternative stimuli; Fisher et al, 1998;Hagopian et al, 2005).…”
Section: Multiple Schedulesmentioning
confidence: 95%
“…These results suggest that the stimuli associated with each component (i.e., white circle, red rectangle) functioned as discriminative stimuli. Subsequent studies have shown that similar stimulus control can be established even when only one component schedule is signaled (Fisher, Kuhn, & Thompson, 1998;Jarmolowicz, DeLeon, & Contrucci-Kuhn, 2009). …”
Section: Multiple Schedulesmentioning
confidence: 97%
See 1 more Smart Citation